This thing of darkness : perspectives on evil and human wickedness - Hamilton, Richard Paul; Breen, Margaret Sönser (At the interface/probing the boundaries, 2004)
Written across the disciplines of art history, literature, philosophy, sociology, and theology, the ten essays comprising the collection all insist on multidimensional definitions of evil. Taking its title from a moment in Shakespeare's Tempest when Prospero acknowledges his responsibility for Caliban, this collection explores the necessarily ambivalent relationship between humanity and evil. To what extent are a given society's definitions of evil self-serving? Which figures are marginalized in the process of identifying evil? How is humanity itself implicated in the production of evil? Is evil itself something fundamentally human? These questions, indicative of the kinds of issues raised in this collection, seem all the more pressing in light of recent world events. The ten essays were originally presented at the First Global Conference on Perspectives on Evil and Human Wickedness, held in March 2000 in Lady Margaret Hall, Oxford University.